2013
DOI: 10.1603/ec13010
|View full text |Cite
|
Sign up to set email alerts
|

Wing Shape and Size of the Western Corn Rootworm (Coleoptera: Chrysomelidae) is Related to Sex and Resistance to Soybean-Maize Crop Rotation

Abstract: The western corn rootworm, Diabrotica virgifera virgifera LeConte, is a major pest of maize in the United States and more recently, Europe. Understanding the dispersal dynamics of this species will provide crucial information for its management. This study used geometric morphometric analysis of hind wing venation based on 13 landmarks in 223 specimens from nine locations in Illinois, Nebraska, Iowa, and Missouri, to assess whether wing shape and size differed between rotated and continuously grown maize where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 53 publications
2
32
0
Order By: Relevance
“…Previous studies of differences in insect shape showed that GM can be used in pest population studies (Mikac et al 2013;Benítez et al 2014aBenítez et al , 2014bLemic et al 2014). Previous studies of differences in insect shape showed that GM can be used in pest population studies (Mikac et al 2013;Benítez et al 2014aBenítez et al , 2014bLemic et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of differences in insect shape showed that GM can be used in pest population studies (Mikac et al 2013;Benítez et al 2014aBenítez et al , 2014bLemic et al 2014). Previous studies of differences in insect shape showed that GM can be used in pest population studies (Mikac et al 2013;Benítez et al 2014aBenítez et al , 2014bLemic et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Then, an asymmetric component was computed from the differences between the original and reflected copies Klingenberg, Barluenga & Meyer, 2002). A general discussion of how Procrustes distances are used in geometric morphometrics is provided by Mikac et al (2013). To assess the significance of DA relative to ME, the left and right wings of 30 individual beetles were digitized twice .…”
Section: Morphometric Analysismentioning
confidence: 99%
“…approximately 1996) to the present time (2011) have revealed minimal genetic differences between populations and among regions (Lemic et al, 2013). Mikac, Douglas & Spencer (2013) recently used wing shape and size as a population marker to demonstrate that differences in hind wing shape were detectable among D. v. virgifera sampled from maize-soybean rotation resistant and susceptible populations in the USA. Indeed, Bouyer et al (2007) was able to demonstrate this for the tsetse fly Glossina palpalis gambiensis Vanderplank, when comparing wing shape and size differences with population genetic differences along an ecological cline, where geometric morphometrics analysis of wing shape and size demonstrated clinal differences, a result that was not mirrored by the microsatellite markers used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…shape analysis) renders the quantification of wing morphology (size and shape) a readily accessible tool for investigating population or geographic differences and for possibly inferring dispersal ability . Geometric morphometric is useful in quantifying the morphological variation within and among species, and geometric morphometric methods begin with the collection of two‐ or three‐dimensional coordinates of biologically definable landmarks, such as hind wing vein intersections in WCR . However, morphometric data are yet to be used to assist in the monitoring of existing or new populations or to inform or evaluate management practices by country or region.…”
Section: Introductionmentioning
confidence: 99%